Jews and Christians in the First and Second Centuries. - Schwartz, Joshua J. (Compendia Rerum Iudaicarum ad Novum Testamentum, 2017)
This volume discusses crucial aspects of the period between the two revolts against Rome in Judaea that saw the rise of rabbinic Judaism and of the separation between Judaism and Christianity. Most contributors no longer support the 'maximalist' claim that around 100 CE, a powerful rabbinic regime was already in place. Rather, the evidence points to the appearance of the rabbinic movement as a group with a regional power base and with limited influence. The period is best seen as one of transition from the multiform Judaism revolving around the Second Temple in Jerusalem to a Judaism that was organized around synagogue, Tora, and sages and that parted ways with Christianity.